Behaviour of Reinforced Concrete Beams With Circular Transverse Openings Under Static Loads - Ling Jen Hua; Howe Sheng Tang; Wen Kam Leong; How Teck Sia (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2020)
Transverse opening in a reinforced concrete beam allows the crossing of mechanical and electrical services through the beam. However, it affects the strength of a beam. Understanding its structural behaviour is crucial to ensure a safe design of the beam. For that, an experimental study was carried out on reinforced concrete beams with circular transverse openings. The four-point load test was conducted to study the effects of the size and the position of the opening on the beam performance under the shear and flexural loads. In addition, three reinforcing methods for the opening were tested. The beams were evaluated in terms of the load-displacement responses, mechanical properties, deflections, and failure modes. The opening with the diameter not exceeding 0.25 times beam height affected about 20% of beam strength (without reinforcements at the opening). The diagonal bar reinforcing method effectively restored the beam strength for the opening size not exceeding 1/3 of beam height. The equation model proposed conservatively predicted the ultimate capacity of the beam with a transverse opening.